A framework for maximizing the benefit from retaining regrowth on private land - Hannah Thomas; Jeremy S. Simmonds; Michelle S. Ward; Laura J. Sonter; Martine Maron (Conservation Biology, 2026)
Conservation interventions often have lower‐than‐desired positive impacts, as revealed by retrospective counterfactual‐based evaluations. To address this, a prospective counterfactual‐based approach can be used to estimate potential benefits and design conservation interventions to maximize outcomes. We developed a framework for estimating the expected benefit of retaining natural regeneration of forest and woodland ecosystems (hereafter regrowth ). First, we considered the additionality of retaining regrowth, by developing a model of deforestation risk. Second, we considered the potential habitat value that the regrowth provides to 29 threatened species, based on expert‐elicited estimates for each species that account for regrowth age. Then, we combined this information to identify where retention of regrowth would yield the greatest additional benefits. Applying this framework to a case study in Queensland, Australia, which contains globally significant deforestation rates and exceptional biodiversity, we found that areas with the greatest expected benefit from retaining regrowth differ greatly when both averted loss of regrowth clearing and threatened species habitat are considered together, versus when these factors are considered individually. We also found that most (56%) of the highest expected benefit areas (i.e., above the 90th percentile) were consistently identified regardless of whether species were treated equally or weighted based on their threatened status or proportion of habitat occurring in regrowth. Our results can help guide conservation investment in the region, and we recommend a similar approach be used more broadly when designing conservation interventions to maximize benefits.

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Characterising Migratory Bird Assemblages in Understudied Regions by Integrating Radar and Citizen Science Data - Xu Shi; Rohan H. Clarke; Jeremy S. Simmonds; Ailsa Kerswell; William Holden; Jason W. Chapman; Richard A. Fuller (Global Ecology and Biogeography, 2025)
Aim Migratory birds are declining globally. In regions where bird migration patterns remain poorly documented, comprehensive data and tools are needed to advance conservation efforts, support sustainable development and fulfil international biodiversity commitments. We aim to enhance understanding of migratory birds in understudied regions by quantifying migration dynamics and identifying overlooked species, using Eastern Australia as a model to demonstrate how multi‐method approaches can resolve uncertainties in migration patterns. Location Eastern Australia. Time Period 2018–2022. Major Taxa Studied Migratory birds. Methods We estimated migration phenology from eBird data in ten regions across Eastern Australia based on abundance changes of species throughout the year; we cross‐validated phenology estimates with those estimated from movement traffic measured by weather radar. We identified species with movement indicative of migration in each region and investigated their legal protection status in Australia. Results Radar and eBird data showed strong correlations in mid‐latitude regions (Victoria to Southeast Queensland), with median migration dates aligning closely, but weaker agreement in Tasmania and tropical Queensland. We identified 311 species with fluctuations of relative abundance suggestive of migration—far exceeding prior estimates—averaging > 90 migratory species per region. Eleven of 18 avian orders included migratory taxa, but legal protection varied: 70% of migratory Charadriiformes (e.g., internationally migrating shorebirds) were listed under national law. In contrast, Passeriformes, Psittaciformes, Anseriformes, primarily moving within Australia, have lower representation, with only 19% of identified Passeriformes formally protected. Main Conclusions This study uncovers a hidden diversity of migratory birds in Australia, many of which lack formal protections, especially short‐distance and intracontinental migrants. We recommend additional conservation measures and targeted surveys focused on these species to better assess threats and support nature‐positive development, including potentially impactful renewable energy projects. Our approach—combining radar and citizen science data—offers a replicable framework to document and protect poorly understood migratory systems globally.

The value of regrowth forests and woodlands for threatened fauna species - Hannah Thomas; Jeremy S. Simmonds; Michelle Ward; Teresa J. Eyre; Martine Maron (Biological Conservation, 2025)

Poor compliance and exemptions facilitate ongoing deforestation - Hannah Thomas; Michelle S. Ward; Jeremy S. Simmonds; Martin F. J. Taylor; Martine Maron (Conservation Biology, 2025)
Many nations are struggling to reduce deforestation, despite having extensive environmental protection laws in place and commitments to international agreements that address the biodiversity and climate crises. We developed a novel framework to quantify the extent to which contemporary deforestation is being captured under national and subnational laws. We then applied this framework to northern Australia as a case study, a development and deforestation hotspot with ecosystems of global significance. First, deforestation may be compliant under all relevant legislation, either through assessment and approval or because of exemptions in the legislation. Second, deforestation may be compliant under at least one relevant law, but not all. Third, there may be no evidence of deforestation assessment or exemption from assessment, despite their apparent requirement, which could mean the deforestation is potentially noncompliant. Finally, deforestation may occur in an area or under circumstances that are beyond the intended scope of any relevant legislation. All deforestation that we analyzed was hypothetically covered by one or more laws. However, 65% of deforestation was potentially noncompliant with at least one law. Because multiple laws could be relevant to a given clearing event, the majority of clearing was still compliant with at least one law, but of these events, only a small proportion was explicitly approved (19%). The remaining were permitted under various exemptions. Of all the legislation we analyzed, most of the exempt clearing occurred under one subnational law and most potentially noncompliant clearing occurred under one national law. Our results showed that even a nation with a suite of mature environmental protection laws is falling well short of achieving international commitments regarding deforestation. Our framework can be used to pinpoint the pathways of policy change required for nations to align local laws with these international accords.

Global assessment of the biodiversity safeguards of development banks that finance infrastructure - Divya Narain; Laura J. Sonter; Alex Mark Lechner; James E. M. Watson; Jeremy S. Simmonds; Martine Maron (Conservation Biology, 2023)
Infrastructure development is a major driver of biodiversity loss globally. With upward of US$2.5 trillion in annual investments in infrastructure, the financial sector indirectly drives this biodiversity loss. At the same time, biodiversity safeguards (project‐level biodiversity impact mitigation requirements) of infrastructure financiers can help limit this damage. The coverage and harmonization of biodiversity safeguards are important factors in their effectiveness and therefore warrant scrutiny. It is equally important to examine the extent to which these safeguards align with best‐practice principles for biodiversity impact mitigation outlined in international policies, such as that of the International Union for Conservation of Nature. We assessed the biodiversity safeguards of public development banks and development finance institutions for coverage, harmonization, and alignment with best practice. We used Institute of New Structural Economics and Agence Française de Développement's global database to identify development banks that invest in high‐biodiversity‐footprint infrastructure and have over US$500 million in assets. Of the 155 banks, 42% ( n = 65) had biodiversity safeguards. Of the existing safeguards, 86% (56 of 65) were harmonized with International Finance Corporation (IFC) Performance Standard 6 (PS6). The IFC PS6 (and by extension the 56 safeguard policies harmonized with it) had high alignment with international best practice in biodiversity impact mitigation, whereas the remaining 8 exhibited partial alignment, incorporating few principles that clarify the conditions for effective biodiversity offsetting. Given their dual role in setting benchmarks and leveraging private finance, infrastructure financiers in development finance need to adopt best‐practice biodiversity safeguards if the tide of global biodiversity loss is to be stemmed. The IFC PS6, if strengthened, can act as a useful template for other financier safeguards. The high degree of harmonization among safeguards is promising, pointing to a potential for diffusion of practices.

Effectiveness of conservation interventions for Australian woodland birds: A systematic review - Jessica C. Walsh; Michelle R. Gibson; Jeremy S. Simmonds; Helen J. Mayfield; Clare Bracey; Courtney B. Melton; April E. Reside; Martine Maron (Biological Conservation, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Wilderness forms and their implications for global environmental policy and conservation - Katharina‐Victoria Pérez‐Hämmerle; Katie Moon; Rubén Venegas‐Li; Sean Maxwell; Jeremy S. Simmonds; Oscar Venter; Stephen T. Garnett; Hugh P. Possingham; James E. M. Watson (Conservation Biology, 2022)
With the intention of securing industry‐free land and seascapes, protecting wilderness entered international policy as a formal target for the first time in the zero draft of the Post‐2020 Global Biodiversity Framework under the Convention on Biological Diversity. Given this increased prominence in international policy, it is timely to consider the extent to which the construct of wilderness supports global conservation objectives. We evaluated the construct by overlaying recently updated cumulative human pressure maps that offer a global‐scale delineation of industry‐free land as wilderness with maps of carbon stock, species richness, and ground travel time from urban centers. Wilderness areas took variable forms in relation to carbon stock, species richness, and proximity to urban centers, where 10% of wilderness areas represented high carbon and species richness, 20% low carbon and species richness, and 3% high levels of remoteness (>48 h), carbon, and species richness. Approximately 35% of all remaining wilderness in 2013 was accessible in

Communicating the true challenges of saving species: response to Wiedenfeld et al. - James E. M. Watson; Jeremy S. Simmonds; Michelle Ward; Chuan J. Yong; April E. Reside; Hugh P. Possingham; Andrew Rogers; Josie Carwardine (Conservation Biology, 2022)

Offsetting impacts of development on biodiversity and ecosystem services - Laura J. Sonter; Ascelin Gordon; Carla Archibald; Jeremy S. Simmonds; Michelle Ward; Jean Paul Metzger; Jonathan R. Rhodes; Martine Maron (Ambio, 2020)

A composite measure of habitat loss for entire assemblages of species - Jeremy S. Simmonds; James E. M. Watson; Alvaro Salazar; Martine Maron (Conservation Biology, 2019)
Habitat destruction is among the greatest threats facing biodiversity, and it affects common and threatened species alike. However, metrics for communicating its impacts typically overlook the nonthreatened component of assemblages. This risks the loss of habitat going unreported for species that comprise the majority of assemblages. We adapted a widely used measure for summarizing researcher output (the h index) to provide a metric that describes natural habitat loss for entire assemblages, inclusive of threatened and nonthreatened species. For each of 447 Australian native terrestrial bird species, we combined information on their association with broad vegetation groups with distributional range maps to identify the difference between the estimated pre‐European and current extents of potential habitat, defined as vegetation groups most closely associated with each species. From this, we calculated the loss index (LI), which revealed that 30% of native birds have each lost at least 30% of their potential natural habitat (LI = 30). At the subcontinental scale, LIs ranged from 15 in arid Australia to 61 in the highly transformed southeastern part of the country. Different subcomponents of the assemblage had different LI values. For example, Australia's parrots ( n = 52 species) had an LI of 38, whereas raptors ( n = 32 species) had an LI of 25. The LI is simple to calculate and can be determined using readily available spatial information on species distributions, native vegetation associations, and human impacts on natural land cover. This metric, including the curves used to deduce it, could complement other biodiversity indices if it is used for regional and global biodiversity assessments that compare the status of natural habitat extent for assemblages within and among nations, monitor changes through time, and forecast future changes to guide strategic land‐use planning. The LI is an intuitive tool that can be used to summarize and communicate how human actions affect whole assemblages, not just threatened species.

The Scale-Dependent Role of Biological Traits in Landscape Ecology: A Review - Andrés Felipe Suárez-Castro; Jeremy S. Simmonds; Matthew G. E. Mitchell; Martine Maron; Jonathan R. Rhodes (Current Landscape Ecology Reports, 2018)